The neural inhibition network is causally involved in the disembodiment effect of linguistic negation. (February 2022) - Vitale, Francesca; Monti, Ilaria; Padrón, Iván; Avenanti, Alessio; de Vega, Manuel
Abstract: Negation applied to action contexts reduces the activation of the motor system. According to the Reusing Inhibition for Negation (RIN) hypothesis, such "disembodiment" effect occurs because understanding negations engages the reuse of inhibitory control mechanisms. Here, we investigated whether the right inferior frontal gyrus (rIFG) – a key area of the inhibitory control system – contributes to primary motor cortex (M1) processing of negated action-sentences. Using a perturb-and-measure paradigm, we applied off-line low-frequency repetitive TMS (rTMS) over the rIFG, before performing a reading task involving action and attentional sentences presented in both affirmative or negative form. During the reading task, motor excitability was assessed by recording motor-evoked potentials (MEPs) induced by single-pulse TMS (spTMS) over the left M1, at two loci in the sentence: the verb or the object. Results show that after sham stimulation (baseline), motor excitability measured on the verb, was reduced for negative, compared to affirmative action sentences. Crucially, neuromodulation of rIFG suppressed this inhibitory effect of negation, since motor excitability was equaled for negative and affirmative action sentences. As expected, no effect of negation was observed for attentional sentences or when the pulse was delivered over the object. Our study confirms that understanding negative action sentences inhibits M1. This effect took place at an early stage of semantic processing (i.e., while processing the verb in our task), and faded at a later time-point. Critically, by highlighting a causal role of rIFG in this motor inhibition, we provide direct neurophysiological support to the RIN hypothesis.